(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Kiranaputri G, Sjahfirdi L, Tumbelaka LITA, Yana A, Priyanto SK, Anggarsari LY, Marizal. 2021. Positive reinforcement conditioning as Sumatran tiger’s (Panthera tigris sumatrae) social enrichment at Tambling Wildlife Nature Conservation Rescue Centre, Lampung, Indonesia. Biodiversitas 23: 55-61. Tiger individuals are translocated to ex-situ conservations due to human-tiger conflicts and may express behavioral change (stereotypic) in captivity. Furthermore, medical check-up routines may cause injury and stress between tiger and operators under tough circumstances. Positive reinforcement conditioning (PRC) is a well-known method to minimize the risks on medical examination and as social enrichment. Therefore, the purposes of this research are (i) to examine PRC on tiger’s blood sample collections and (ii) the correlation between physiological stress and tiger’s stereotypic behavior (SB) through the neutrophil per lymphocyte ratio (N/L ratio) method. Four Sumatran tigers’ (1 female, 3 males) behavior were observed using focal animal sampling at Tambling Wildlife Nature Conservation Rescue Centre, Lampung, Indonesia. Each baseline and post-enrichment tiger’s behavioral observations were conducted for 1.920 minutes (1 male & 1 female) and 960 minutes (2 males). Then SB was categorized into low (<33,33%), intermediate (33,34-66,66%) or high (>66,67%). Blood collections (BC) were conducted twice (1st without PRC and 2nd with PRC) directly on the tiger after the behavior observation. Tiger’s physiological stress during BC was analyzed with Wilcoxon. The correlation between physiological stress and SB was analyzed with Kruskal-Wallis. All tigers’ N/L ratios were in normal value from this present research during both BC. The tigers did not show chronical stress as long this research was conducted. PRC was significantly effective to reduce tiger physiological stress during BC (Z= -0,730, P= 0,465 < 0,05). All tigers showed low (<33,33%) pacing SB (without fur-plucking, self-biting, and self-mutilation behavior) both in baseline and post-enrichment. Any fur-plucking, self-biting & self-mutilation behaviors were not observed. Physiological stress was not correlated to SB ( = 3, P= 0,392 > 0,05). The PRC was an appropriate and effective tool to handle Sumatran tigers during BC. These tigers performed SB as a coping mechanism in the enclosure.